Permit Issues of Online Single Submission (OSS) - Desi Ayuwati Ayuwati; Gunarto Gunarto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The purpose of this study was to: 1) To analyze the implementation problems of Online Single Submission (OSS) in Indonesia. 2) To analyze the constraints and find solutions permitting the implementation of Online Single Submission (OSS) in the PTSP.The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analytical method. Based on the results of data analysis concluded that: 1) Problems OSS among others: first, Presidential Regulation No. 24 of 2018 does not set the transition effect. Secondly, the OSS system is not ready, partly because of computer systems across ministries and agencies, both at central and local levels that have not been connected properly. CMEA Nasution admitted that the government has not fully prepared to implement OSS. Third, related NSPK of K/L and LGs. 2)Presidential Regulation No. 24 of 2018 has been set PTSP but only the definition in Article 1 point 28 and General Explanation of PTSP. In General Explanation mentioned that Presidential Regulation No. 24 of 2018 perfecting the OSS on the central government and local governments to become more efficient, serve, and modern. In the body of Presidential Regulation No. 24 of 2018 no provisions to the PTSP. The absence of regulation PTSP in Presidential Regulation No. 24 of 2018 lead to confusion in practice, given the PTSP is a designated institution Article 25 paragraph (4) and (5) Investment Law.